Peran moderasi kesadaran merek halal pada pengaruh pengetahuan produk dan keterlibatan produk terhadap pengambilan keputusan pembelian (studi pada konsumen hokben di daerah istimewa yogyakarta) - Sutrisno Wibowo; Dito Prakosa Wijaya (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to analyze the influence of product knowledge and product involvement on purchase decision-making, and to examine the moderating role of halal brand awareness in this relationship. The research object is the Japanese fast food restaurant HokBen, with HokBen consumers in the Special Region of Yogyakarta as the subjects. This study used a quantitative approach with a survey method. Primary data was obtained by distributing questionnaires to 170 respondents selected using a purposive sampling technique. Data analysis was performed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method using SmartPLS software. The results show that product knowledge has a positive and significant effect on purchase decision-making. Product involvement also has a positive and significant effect on purchase decision-making. Furthermore, halal brand awareness has been shown to moderate the relationship between product knowledge and purchase decision-making. However, halal brand awareness has not been shown to moderate the relationship between product involvement and purchase decision-making